Dendrophylliidae cold-water corals in a warm ocean: The effect of exposure duration on their physiological response. (November 2021) - Reynaud, Stéphanie; Orejas, Covadonga; Campagno, Andrea; Rottier, Cécile; Jimenez, Carlos; Ferrier-Pagès, Christine
Abstract: Deep-sea reef ecosystems are hotspots of biodiversity but are particularly threatened by seawater warming, because the species that live there have evolved within a narrow thermal range. The degree to which cold-water corals (CWCs), the reef builders, can acclimate to changes in their thermal environment requires more investigation. Our study is one of the very first to assess the thermal performance of Dendrophylliidae CWCs on a 2-year basis. Colonies of Dendrophyllia cornigera and D. ramea, collected in the Mediterranean Sea, were exposed during 2 years to their natural mean temperatures (referred as control temperature, CT) or to temperatures being 4 °C (T+4) and 8 °C (T+8) higher. A 4 °C decrease in temperature (T-4) was also tested for D. ramea . Several physiological parameters, such as rates of growth, calcification, and respiration, as well as total organic carbon release were measured after 2 and 20 months of treatment. The results obtained show that Dendrophylliidae corals are able to survive a +4 °C over a two-year period, and even a +8 °C for D. ramea . The elevation in temperature induced a transient increase in all physiological parameters. However, after 20 months, parameters were significantly decreased compared to the first measurement. At the end of the experiment, growth rates were even significantly lower at T+4 and T+8 compared to the control temperature, suggesting that the coral lifespan is significantly reduced over the long term. Finally, we observed a positive relationship between respiration and calcification rates in these corals, suggesting that the calcification process is dependent on the inorganic carbon provided by respiration. Overall, this study shows that physiological processes in CWC species are slow and that long-term incubations are necessary to predict the impact of climate change on their survival capacities.